A dual-responsive humidity sensitive-based cellulose paper: A fabrication of smart strip from sustainable nanoclay and graphite-beeswax composite - Abu Hannifa, Abdullah; Wan Farhana, W. Idris; Ainizar, Mustapa; Zulhelmi, Ismail (Elsevier Ltd, 2023)
A highly humidity-responsive paper can detect moisture or OH-attached molecules at the sub-micron or nano level range. Applying hydrophilic nanoclay as an active material for water sensing would reduce the fabrication cost while remaining environmentally friendly. In this communication, we report the preparation of a nanoclay-inspired dual-responsive smart film that can signal humidity levels from mechanical and electrical responses. The paper will bend as the nanoclay layer swells whereas the resulting bending strain will trigger the electrical resistance changes in the hydrophobic electrically conductive graphite-beeswax layer.